The Effect of Coffee Skin Composition on Planting Media on the Growth and Production of Wood Ear Mushrooms and Oyster Mushrooms - Safarudinsyah; Ikhwan, Ali; Ishartati, Erny (Universitas Muhammadiyah Malang, 2021)
This study evaluated the interaction between mushroom species (ear mushrooms and oyster mushrooms) and growing media (with the addition of coffee peels) on mushroom growth and yield. The results showed that oyster mushrooms were superior to ear mushrooms in various parameters, including mycelial growth, time to first primordia emergence, harvest wet weight, and dry weight. The use of media with the addition of 20% coffee skin showed good results, with significant mushroom growth and yield. This research was conducted at the Production Unit of the Integrated Land Biotechnology Development Center, Faculty of Agriculture and Animal Husbandry, Muhammadiyah University of Malang from November 2019 to January 2020. This research used an experimental method with two types of mushrooms and three different compositions of growing media. The results of data analysis showed significant differences between treatments, with oyster mushrooms showing better results than ear mushrooms. These results can be a guideline for oyster mushroom cultivation by utilizing coffee skin waste as an effective growing medium.